The healthcare system personnel provision as a prerequisite for the transition to the knowledge economy - Mishchenko, I. V.; Mishchenko, V. V. (Journal of Economic Research & Business Administration, 2023)
One of the basic principles of the knowledge economy is the availability of labor resources. This principle is especially important for the healthcare system, where the life and health of people depend on the qualifications and skills of doctors. In Russia, as in many other countries, there is a shortage of doctors, which has worsened during the COVID-19 pandemic. The purpose of the study is to analyze the staffing of the Russian healthcare system, on the basis of which to propose ways to overcome the shortage of personnel in it. Traditional methods of quantitative analysis were used in the work. Secondary data from the information and analytical system of the Federal State Statistics Service of the Russian Federation served as data sources. The study of the personnel component of the health care system in Russia revealed that the shortage of personnel is typical, first of all, for regions with a low standard of living of the population. There are also disproportions in the various specialties of training. In general, the Russian health care system is characterized by a low level of remuneration with its high intensity. The Russian Government is making significant efforts to eliminate the problem, but these measures do not give the expected effect. The practical significance of the work lies in the development of specific recommendations for the authorities to address the shortage of personnel in the health care system. As measures, it is proposed to use the Soviet experience of planning in the health care system (centralization of planning). At the same time, it is worth paying attention to the best practices of other countries. Only using an integrated approach, it is possible to overcome the problem of shortage of personnel in Russian healthcare and make the transition to a knowledge economy.